The story of the "now-women": changing gender norms in rural West Africa. Issue 2 (17th February 2018) - Cislaghi, Beniamino
ABSTRACT: This article offers a qualitative investigation of how human rights education sessions, embedded in a multi-faceted intervention, helped members of a rural community in West Africa challenge inequitable gender norms that hindered women's political participation. Results show a change in women's political participation and community members' descriptions of women's potential. Three features of the intervention contributed to this change: (1) its pedagogical approach; (2) its substantive content; and (3) the engagement of men and women together. The article calls for interventions that facilitate sustained dialogue between men and women to achieve greater gender equity.